LEARNING STYLE IN LEARNING PRONUNCIATION OF EFL LEARNER - Yasmika Baihaqi; Bambang Eko Siagiyanto; Rahmad Adhi Pamungkas (Premise: Journal of English Education and Applied Linguistics, 2021)
The people usually ignore pronunciation when speaking, telling something, discussing, singing, etc. The focus of this research is to explore the learning style of an EFL learner named Kharis  Fikril Muhorobin in practicing pronunciation. The design of this research is a case study in the form of qualitative research design. The objective of this research is finding the learning style of an EFL learner. This research was conducted on campus and in the informant's boarding house. The data were collected by using triangulation involving observation, interview, and documentation. The analysis of the data was conducted using descriptive analysis. The result shows that  the informant focused on British pronunciation. Based on the result of data analysis, it is found that there are three strategies applied by an informant in practicing British pronunciation. Those strategies are listening and practicing English songs, watching, and listening to English movies,   and reading out loud English books